Performance Analysis of Centrifugal Pump Head in Series and Parallel Circuit - Wilarso; Rendi Reshudin (Universitas Medan Area, 2025)
When the pump starts working and the fluid flow capacity is different from the pump capacity, an analysis is performed on the head value obtained from the pump whose value is insufficient to the required capacity. Analysis of the pump head capacity value is necessary to ensure that the pump can operate efficiently and according to system requirements. The method used to calculate the pump head value includes a theoretical approach and quantitative calculations. The pump head calculation is carried out by applying the Reynolds equation and other fluid mechanics principles, as well as considering factors such as flow velocity, pipe diameter, and fittings or supporting components used. The purpose of this analysis is to determine and calculate the optimal pump head value in a series or parallel arrangement so that the system can work under ideal conditions. The results of this study indicate that the pump head in a series arrangement is 3.9 m, while the Head value for a parallel arrangement is 2.2 m. The head loss value for the series arrangement is 0.000007108 or 71.08 ×10^-6, while the head loss value for the parallel arrangement is 0.000001197 m or 11.97 ×10^-6. Pumps with a series configuration are used to obtain higher pressures. Pumps with a parallel configuration are used to obtain larger flow rates.